ASPEKHUKUMTERHADAP PERS - Murani, Asnawi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2009)
Press freedom in Indonesia "is not apart from its accountabilities for particular delicts asset for thin Press Actand Criminal Law currently revised in line with the development of era and Indonesian cultures. Accountabilities of the press for delicts including humiliation, slandering, and pornography where such involved parties shall account for.Meanwhile, legal aspects for such involvedParties include editor, writer, publisher, printing agency and distributors, with more advant ageous legal position compared to the ones of hon-pressdelicts